The motivations of Chinese individual foreign investors in the Australian residential real estate market - Wu, Po-Jui; Chen, Athena Ying (International Journal of Strategic Property Management, 2022)
There is an increasing number of Chinese individual foreign investors (IFIs) in Australian residential real estate markets, but few studies specifically focus on Chinese IFIs and comprehensively analyse these investors’ motivations in the Australian real estate market. This paper examines the motivations of IFIs in the Australian residential real estate markets. A qualitative historical research approach was employed to examine the topic. By using semi-structured interviews of Chinese individual investors (consisting of Chinese temporary residents and Chinese nonresidents) and Australian agents in Australian residential real estate from 2014 to 2015, the paper finds four common motivations (good living environment, stable political environment, cost efficiency and profit returns) and three distinct motivations (education, immigration and bandwagon effects) of Chinese IFIs. It was found that cost efficiency, profit returns, education investment and immigration tend to be articulated differently between Chinese temporary residents and Chinese nonresidents, although these four motivations were expressed by both. Chinese nonresidents consider cost efficiency and profit returns as their major motivations. In contrast to Chinese nonresidents, education, and immigration are the most important motivations instead of some traditional motivations such as profit returns or cost efficiency for Chinese temporary residents.